PENERAPAN SIX SIGMA UNTUK ELIMINASI WASTE PADA PT XYZ BAGIAN GARMENT - Fakhri Turmudzi; Julio Keviin Marsxonery sNadeak; Nanda Tri Amalia (LPPM Universitas Bina Bangsa, 2022)
A production process that pays attention to quality will produce a quality product and free from damage. This can avoid waste and inefficiencies so that production costs can be reduced or can be more efficient. Six sigma is one of the methods that applies principles to be able to achieve the targets that are met. PT XYZ with the Garment section is a part that focuses on producing baby clothing products. The results of the observations found that there were 13 types of defects recorded during 20 working days. Furthermore, improvements were made through six sigma with the stages of data collection, data processing, and data analysis. The results are known to still have a process outside the control map, so an analysis of rejects was carried out within 20 working days. Repair or defects that are most dominant become CTQ, namely 3 types of repairs or defects are Position / Label Brand & Size Not Suitable, Stitches Missed / Broken and Defects of Raw Materials. With percentages of 44.66%, 16.07% and 7.98%. From the production data carried out by Quality Control Garment in 20 working days as many as 44789 pcs with the number of repair products or defects that occurred amounted to 813 pcs